Komunikasi Edukasi untuk Pencegahan Penularan Covid-19 dan Peningkatan Derajat Kesehatan Masyarakat di Kabupaten Serang Banten - Ail Muldi; Damanhuri Damanhuri; Ameliana Putri (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
Location of Sukalaba village located in the hilly area and far away which causing to lack of attention and monitoring by the regional government. The main problem of Sukalabans is disease threat because they are lack of knowledge and awareness in implementing health protocols and the garbage is not managed causing lots of flies around the settlement as a result of the large number of chicken farms. Focus of these service activities are public health and environment aspect. These activities aimed to change community behavior which led to a clean and healthy lifestyle (PHBS) to prevent disease transmission including covid-19, increase community hygiene and environmental health. The applied approach is communication approach with Extended Parallel Process model which focused to components of message, perception, and self-efficacy. The results of community activities covered educational communication of preventing of Covid-19 transmission, integrated waste management planning, and door-to-door counseling about use of fly poison. Other supporting activities are healthy exercise regularly, community service to mosque cleanliness, and planting 1000 trees.